On Solaropsis Beck: New anatomical data and its systematic position within the Helicoidea (Pulmonata: Stylommatophora) - Cuezzo, Maria Gabriela (2002)
New anatomical data for three species of the genus Solaropsis Beck, 1837, is provided. The descriptions were based on gross mophological studies of the genital, pallial, digestive and nervous systems. Based on the present descriptions and the published anatomical information of different species of the genus their relationships within the Helicoidea are discussed. Psadara Miller, 1878, a formerly desribed subgenus of Solaropsis, later considered as a different genus, is currently not considered a natural group. The results of this study support the idea that Solaropsis should be included within the Camaenidae.